Identifikasi Tingkat Kerusakan Bangunan Gedung Sekolah Dasar (Studi Kasus di Kecamatan Gandus Kota Palembang) - Pratiwi, Zakiah; Rachman, Delli Noviarti; Immadudin, Muhamad (Universitas Muhammadiyah Palembang, 2025)
One of the government's responsibilities is to educate the nation. Supporting this is by supporting good facilities and infrastructure, including the State Elementary School building. This study took samples from 3 elementary schools in Gandus District. The purpose of this study is to identify the types of damage, the classification of the percentage of damage, and the estimated cost for rehabilitation in the 3 buildings. The research method is by surveying the location. Based on the results of the research that has been carried out, it was found that SDN 142 was Lightly Damaged with a value of 4.36%, SDN 143 Building D was Heavily Damaged with a value of 57.00%, and SDN 146 Building B was Lightly Damaged with a value of 9.87%, Student Toilets were Lightly Damaged with a value of 15.02% and the Library was Lightly Damaged with a value of 10.71%. The estimated cost of rehabilitation of Building A SDN 142 is Rp. 54,449,000.-, the estimated cost at SDN 143 is Rp. 905,935,000, and the estimated cost at SDN 146 Palembang is Rp. 92,831,000.-.